2018
DOI: 10.1111/tmi.13035
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of epilepsy in Bhutan

Abstract: Summary Objective: To assess the economic impact of epilepsy in Bhutan, a lower-middle-income country with a universal health care system, but with limited access to neurological care. Methods: A cross-sectional survey was conducted of patients with epilepsy receiving care at Jigme Dorji Wangchuk National Referral Hospital from January to August, 2016. Data were collected on clinical features of epilepsy, cost of care, impact of epilepsy on school or work, and household economic status of participants and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
(28 reference statements)
4
13
0
Order By: Relevance
“…Nevertheless, nearly 60% of PWE experience adverse effects from AEDs that could result in a significant decline in the quality of life . In addition, PWE face a substantial economic burden because of the long‐term use of AEDs . Withdrawal from AEDs is an obvious means to avoid the adverse influences of taking AEDs, but approximately 34% of PWE treated only with medication will have seizure recurrence after the withdrawal of AEDs .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, nearly 60% of PWE experience adverse effects from AEDs that could result in a significant decline in the quality of life . In addition, PWE face a substantial economic burden because of the long‐term use of AEDs . Withdrawal from AEDs is an obvious means to avoid the adverse influences of taking AEDs, but approximately 34% of PWE treated only with medication will have seizure recurrence after the withdrawal of AEDs .…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is characterized by frequent and unpredictable disruptions of brain functions resulting in “epileptic seizures.” Epilepsy has a great impact on the quality of life through increased incidence of injury and death, unemployment rates, lower monthly incomes, higher household costs and high absenteeism at work and schools (Jennum et al, 2017 ; Trinka et al, 2018 ; Wibecan et al, 2018 ). An epileptic seizure is considered as a transient episode of signs or symptoms, including transitory confusion, staring speech, irrepressible jerking movements, loss of consciousness, psychic symptoms such as fear and anxiety, due to the abnormal synchronous neuronal activity of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The negative CI indicated that countries with low levels of socioeconomic development had a higher epilepsy burden. Epilepsy has a significant economic impact on health-care needs, premature death, and disruption of work or education for individuals and their families (4,51). A review of studies estimating the cost of epilepsy reported that the direct and indirect cost per person per year ranged from US$ 1,736 to 5,848 and 2,037 to 8,587, respectively (4).…”
Section: Discussionmentioning
confidence: 99%